The impact of borrowing English words into Iraqi Arabic Dialect - Al Yashil, Ali Abdalkarem M.Sadeq; V.M. Subramanian (UIR Press, 2024)
This paper deals with usage of English borrowing words in Iraqi Arabic dialect as one of the linguistic phenomena that we are currently experiencing due to globalization and the use of English language as a global Language. This study focused on limited borrowing words that are used while conversation used by indirect interview. The study aims to clarify the relationship between the use of words in English and Arabic Language and how there is an impact between these two Languages. The study also aims to use most common words in Iraqi accent Arabic borrowed from English Language. The study further concluded that borrowing allows the recipient language to expend its vocabulary. However, the borrowing from any donor language have to undergo certain processes to make them fit appropriately into the recipient language. This study also deals with the borrowing English words that has penetrated the Iraqi Arabic Language during the past few decades. The process of borrowing from English language took place indirectly due to trade, education, etc., and this brings new words to Arabic Language. The study is based on an analysis through conversation in English activity. The researcher found that there are words taken from English language, but not exactly like English in pronunciation or spelling because of alphabet between two languages and also the influence of mother tongue on language, and this led to a change in pronunciation.